Effect of Adding "Raja" Banana Peel Bioactivator (Musa Textilia) on Tempeh Liquid Waste in Making Organic Liquid Fertilizer - Dewi Randa; Iva Rustanti Eri; Marlik Marlik; Pratiwi Hermiyanti (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: The organic content of tempeh liquid waste and "Raja” banana peel can be utilized to make organic liquid fertilizer as an alternative for waste control. This study aims to analyze the effect of "Raja” banana peel bio-activator on tempeh liquid waste during the production of organic liquid fertilizer. Methods: The research design is a pure experiment with a posttest only and a control group design. The object of the study was tempeh liquid waste treated with Raja banana peel bio-activator in three replicates of 30 mL 40 mL and 50 mL. Data analysis used the Kruskal Wallis test. Results and Discussion: The highest average in C content was found in liquid fertilizer with bio-activator 30 mL (1.84%), N content in liquid fertilizer with bio-activator 50 mL (0.17%), P content in liquid fertilizer with bio-activator 50 mL (0.11%), K content in liquid fertilizer with bio-activator 30 mL (0.13%) and total macro nutrients (N, P, K) in liquid fertilizer with bio-activator 50 mL (0.36%). The average volume of "Raja” banana peel bio-activator did differ significantly between 30 mL, 40 mL and 50 mL, indicating that it did not significantly affect the content of C, N, P and K in organic liquid fertilizer. Conclusion: The contents of macro nutrient in this organic liquid fertilizer do not meet the government standard on Minister of Agriculture Regulation; therefore' further research is needed to determine the appropriate levels of bio-activators in producing organic liquid fertilizer.